Netralitas ASN, TNI, dan POLRI dalam Partisipasi Politik pada Pilkada Tahun 2024 - Purnomo, Teguh (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Bureaucratic neutrality is a system where the bureaucracy will not change in maintaining its services to the public/community. This study aims to (1) Identify and analyze the Political Participation of ASN, TNI, and POLRI, (2) Analyze the Neutrality of ASN, TNI, and POLRI in Political Participation in the 2024 Pilkada, (3) Discuss efforts to overcome violations of ASN, TNI, and POLRI neutrality in the 2024 Pilkada, and (4) Provide contributions to understanding and improvements in, and contribute new perspectives in strengthening understanding related to ASN, TNI, and POLRI Neutrality in Political Participation in the Pilkada. Using a qualitative approach, data was collected through interviews and document studies. The data analysis process is data collection, data display, data condensation, conclusion: drawing/verification. The findings show that 417 reports are suspected of violating ASN neutrality. Violations of neutrality are dominated by ASN siding with certain candidates through social media. There is no violation of TNI neutrality. This study contributes to the handling of ASN, TNI, and POLRI neutrality.